INVESTIGATION ON THE EXISTENCE OF MATHEMATICAL DOMAINS AND CONCEPTS IN THE QURAN - Mohamad Noorisham, N.L.; Abu Bakar, S.; Saian, R. (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Mathematical domains refer to specific sets or areas of mathematics that focus on particular types of objects, structures, or functions. Whilst mathematical concepts are fundamental ideas or principles in mathematics that help us understand and describe various phenomena. This study aims to explore the specific domain of mathematics namely numbers, arithmetic operations, geometry, and measurement that exist in the Quran using an exploratory-qualitative research approach. The investigation reveals that there are a number of verses in the Quran that mentioned about mathematical domains and concepts such as numbers in surah al-Baqarah, an-Nisa’, al-Maidah, an-An’am, al-Anfal, al-Furqan, as-Sajdah, as-Saffat; arithmetic operations in surah al-A’raf, al-Baqarah, al-‘Ankabut, al-Anfal, an-Nisa’; geometry in surah al-Baqarah; and measurement in surah al-Kahf, Yunus, al-Hajj, al-Baqarah, an-Najm. The findings can be used as a supplement idea for the teachers or educators to attract students to enjoy learning mathematics as it relates to their religion and real-life situations.